Roadmap for a systematic review of the literature: The identity of psychology - Costa-Lobo, Cristina (2017)
The systematic review of the literature concerns a scientific method of research and analysis of papers in a particular area of science. In this paper, we present the roadmap of a systematic review of the literature about the identity of Psychology. This systematization precedes a survey about this reality in Portugal, through interviews with Portuguese psychologists. This research stems from questions and reflections about the recognition of the role of psychological intervention in today's societies. Given the great development of the psychological science, as well as the emergence of a wide range of activities that are associated, the need to understand the role of psychologists and psychological intervention becomes relevant. Such considerations created the goal of reflecting on the psychologists' professional identity in the present and, consequently, on the identity of Psychology itself. The present study attempts to shed some light on the phenomena associated to the professional identity of psychologists, namely, by answering one central research question: What is the fundamental and exclusive goal of psychological intervention, and which distinguishes it from any other type of intervention? Moreover, the present study aimed to analyze how psychologists define themselves and are defined by other professionals and by the public in general; to identify the difficulties that psychologists perceive in their functions as professionals; and also, to identify how psychologists interpret and describe their functions. The data that compose the present systematic review of the literature result from the extraction of documents from the following data sources: Web of Science, ELSEVIER Scopus, Scielo, APA PsycNet, Pepsic, CAPES, and b-on. The three main phases in the development of this roadmap (Initiation, Processing, and Exit) are presented. Also, the tasks of the following steps are identified: 1) identification of the need to carry out a systematic review of the literature on the selected theme; 2) elaboration of a proposal for the systematic review and development of the draft revision; 3) selection of databases, descriptors, and studies to be included in the proposal; 4) selection of studies; 5) preparation of the first consensus meeting among researchers; 6) evaluation of study quality; 7) organization of the data to be included in the research; 8) extraction of the data and synthesis of the data obtained; 9) final report, recommendations and transfer of evidence to practice.